2009
DOI: 10.1007/s11136-009-9496-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of physical and mental health summary scores from the patient-reported outcomes measurement information system (PROMIS) global items

Abstract: Background The use of global health items permits an efficient way of gathering general perceptions of health. These items provide useful summary information about health and are predictive of health care utilization and subsequent mortality. Methods Analyses of 10 self-reported global health items obtained from an internet survey as part of the PatientReported Outcome Measurement Information System (PROMIS) project. We derived summary scores from the global health items. We estimated the associations of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
1,257
2
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,493 publications
(1,287 citation statements)
references
References 16 publications
14
1,257
2
14
Order By: Relevance
“…Even with the seemingly strong correlation between the item and the scale, it is possible for the item to have different correlations with a criterion measure. 15 For example, Hays et al 8 found that the PROMIS global physical health scale had a higher polyserial correlation than the single item with the EuroQol EQ-5D (0.82 vs. 0.65). In addition, the respondents to the survey were primarily members of an Internet panel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the seemingly strong correlation between the item and the scale, it is possible for the item to have different correlations with a criterion measure. 15 For example, Hays et al 8 found that the PROMIS global physical health scale had a higher polyserial correlation than the single item with the EuroQol EQ-5D (0.82 vs. 0.65). In addition, the respondents to the survey were primarily members of an Internet panel.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these are administered using five-category response scales, and one item (rating of pain on average) uses a response scale of 0-10: 8 …”
mentioning
confidence: 99%
“…The PF-CAT is based on modern psychometric techniques using item response theory, which has been used in the educational field to optimize test administration for decades by reducing time constraints to the participant, test length, data entry errors, and organizational cost while preserving data efficacy [3,4]. The PF-CAT includes a total of 124 physical function items across five categories related to activities of daily living and the Global10 is a 10-item instrument representing five primary domains (physical functioning, pain, fatigue, emotional distress, social health) with cutoffs across domains [4,5,10]. Both outcome measures have demonstrated appropriate psychometric properties [4,5,10,11].…”
Section: Methodsmentioning
confidence: 99%
“…The PF-CAT includes a total of 124 physical function items across five categories related to activities of daily living and the Global10 is a 10-item instrument representing five primary domains (physical functioning, pain, fatigue, emotional distress, social health) with cutoffs across domains [4,5,10]. Both outcome measures have demonstrated appropriate psychometric properties [4,5,10,11]. Preoperative physical health was assessed using the ASA Physical Status classification system, which is a 6-point categorical scale and evaluates the degree of a patient's physical health before undergoing anesthesia and surgery [24].…”
Section: Methodsmentioning
confidence: 99%
“…21 Anxiety and depression were measured using the Patient Reported Outcomes Measurement Information Service (PROMIS) short form subscales. 22 Anxiety scores ranged from 7 to 35, depression from 8 to 40, and physical function from 0 to 100. Northwestern University's Institutional Review Board approved the study.…”
Section: Measurementmentioning
confidence: 99%